Sensitivity of preparasitic stages of Chordodes nobilii (Gordiida, Nematomorpha) to malathion - Achiorno, Cecilia Luján (2009)
The largest part of the life cycle of Gordiida, known as horsehair worms, occurs in aquatic environments usually affected by agricultural activities. The free-living adults reproduce in freshwater environments, where preparasitic larvae undergo development. Since malathion is an insecticide used in the distribution area of Chordodes nobilii, the aim of this study is to evaluate the effect of malathion concentrations which might be expected in the environment on preparasitic stages of this species. The embryonic development and the viability of larvae were analyzed after a short-term exposure to malathion concentrations ranging between 36 and 220 μg a.i./l. Embryo development was inhibited at 220 μg a.i./l and the infective capacity of larvae derived from malathion-exposed eggs was significantly decreased starting from the lowest concentration. Larvae developed from malathion-exposed eggs exhibited malformations. Directly exposed larvae also showed decreased infectivity since the lowest assayed concentration. Our results indicate that a short-term exposure to malathion at levels potentially present in the surface water in environments inhabited by Chordodes nobilii affects significantly its preparasitic stages and the infective capacity of parasitic larvae.